2-Nitrobenzyl 2-chloroacetate - Zhu, Kai (International Union of Crystallography, 2009)
In the molecule of the title compound, C(9)H(8)ClNO(4), an intramolecular C—H⋯O interaction results in the formation of a near-planar (r.m.s. deviation 0.002 Å) five-membered ring, which is oriented at a dihedral angle of 4.07 (4)° with respect to the adjacent aromatic ring. In the crystal structure, intermolecular C—H⋯O interactions link the molecules into a two-dimensional network.